Spiritual values of education on Karate Kid - Dayana, Yuliana Fatima; Helmanto, Fachri (ETUDE: Journal of Educational Research, 2020)
Background: Â Knowing the movies is most likely a favorite activity, it can take apart in education. Education is one of the important things in our lives. Most adults think Karate Kid is inspiring a violation. It is shown many Kung Fu movements and fighting scenes. However, the process of characters in being someone that would be interesting to be analyzed. It is more like the teaching-learning process to get something of a student.Purpose: This study aims to analyze the characters and find out the educational value shown in this movie. In addition, research has focused on analyzing the spiritual values of education following two items of discussion namely value of giving and value of being.Design and methods: The method in this study uses a descriptive qualitative approach. Next, the analysis is done by watching the movie many times and then continued the analysis by collecting data from books and some Internet resources to find theories related to the topic to be discussed. The next step required to arrange the analysis is to prepare the material by selecting multiple events of the movie and classifying the events related to the analysis.Results: Based on the research finding, there are eight educational spiritual values found in The Karate Kid namely honesty, brave, peace, self-discipline, respect, love and affection, not selfishness, and also kind and friendly.